The Structure of the Chinese Material Value Scale: An Eastern Cultural View - Liao, Jiangqun; Wang, Lei (Frontiers in Psychology, 2017)
This study investigated the structure of the Chinese Material Value Scale (MVS). A 2-factor structure, rather than the original 3-factor structure, was proposed for China by means of confirmatory factor analysis. Direct evidence showed that the dimensions of success and happiness could be merged together. Both explicit and implicit methods were used to examine the relationship between success and happiness based on possession. In particular, as an implicit method, the dot-probe paradigm recording participants’ response time supported the idea that the 2 factors could be merged together. The results also showed that for Chinese people, success to an extent means happiness, while the converse is not necessarily true. Chinese are much more concerned about social evaluation than their own feelings, and this cultural characteristic is reflected in our findings.